Modelos de gestão participativa para unidades de conservação federais de uso indireto: o caso do Parque Nacional da Tijuca - Gonçalves, Gilberto Lamoglia (2009)
This thesis analyses the theoretical landmarks that had involved the protection of natural areas in the world and in Brazil and the effective model of federal Units of Conservation of indirect use in the country. Additionally, it is considered the proposal of participative management, in special the Social Organizations and the Organization of the Civil Society of Public Interest, as alternative of management in the related Units of Conservation. The study of the Tijuca s National Park illustrate the relevancy of the different models of management.